Analysis of Students' Learning Difficulties in Mathematics Subjects for Class V MIM Al-Akbar Pandeyan - Izzatul Laili; Purbowati , Dwi (JENIUS :Journal of Education Policy and Elementary Education Issues, 2024)
Grade V MIM Al-Akbar Pandeyan students generally find it difficult to learn mathematics because they consider it a difficult and scary subject, even though mathematics has an important role in everyday life. This study aims to determine students' learning difficulties and the factors causing students' learning difficulties in mathematics subjects for grade V at MIM Al-Akbar Pandeyan, Ngemplak, Boyolali, in the 2022/2023 Academic Year. This study uses a quantitative descriptive research type. Data collection techniques use tests, questionnaires, and documentation. The results of the study show that: 1) The learning difficulties faced by students in mathematics subjects for grade V consist of two, namely students' difficulties in understanding the concept of material on nets of geometric shapes (cubes and cuboids) and difficulties in problem-solving, namely in arithmetic operations, solving story problems, and changing problem sentences into mathematical sentences; 2) The factors of learning difficulties faced by students in mathematics subjects of grade V at MIM Al-Akbar Pandeyan consist of two factors, namely internal factors (attitude in learning 54.80%, learning motivation 58.97%, physical health 44.87%, and sensory ability 45.19%) and external factors (teacher factors 39.74%, use of learning media 55.13%, school facilities and infrastructure 43.27%, and family environment 46.92%). The results of this study are expected to help teachers design more adaptive learning strategies based on student needs